The Effect Of Return On Equity, Debt To Equity Ratio, And Current Ratio On Profit Growth At Pt Tower Bersama Infrastructure Tbk Period 2015-2024 - Wulandari, Syifa Tri; Fadli, Achmad Agus Yasin (Journal of Management, Economic, and Accounting, 2025)
This study aims to determine the effect of Return On Equity, Debt to Equity Ratio, and Current Ratio on profit growth at PT Tower Bersama Infrastructure Tbk during the period 2015 to 2024. The analysis results show that the Adjusted R square value is 56.9% while the remaining 43.1% is influenced by other factors outside this research model. Partially, Return On Equity has no significant effect on earnings growth with a Tcount value of 2.207 < Ttable 2.447 and a significance of 0.069> 0.05. Debt to equity Ratio has a negative and significant effect on earnings growth with Tcount -3.464 > Ttable 2.447 and a significance value of 0.013 < 0.05. Current Ratio (CR) has no significant effect on earnings growth with Tcount 0.228 < Ttable 2.447 and significance 0.827 > 0.05. Together, the three independent variables have a significant effect on earnings growth, with an Fcount of 4.953> Ftable 4.76 and a significance value of 0.046 <0.05.